Experimental Analysis of Ionic Iron Compounds on Post-Coagulation Floc Settlement under the Presence of Magnetic field in Fly-Ash Media (Global Journal of Science Frontier Research, 2021)
The most abundant and one of the most precious resources (fresh water) for the Survival of life is on the verge of depletion. Hence various treatment processes to treat wastewater have and are being researched. Speaking about waste, another recent waste comes into the picture which is available in abundance and easily accessible commonly known as Flyash. Multiple research have been done in order to utilize the components of fly ash for removal of heavy metal like Arsenic, Cadmium, and Nickle etc. for the past years. This paper is based on the idea of utilization of the magnetic property of the Nano iron particles (Fe2+ & Fe3+) present in the fly ash as Fe2O3, as well as the adsorption capacity of the carbon particles present in the fly ash.
Keywords: atomic absorption spectroscopy; fly-ash; turbidity; magnetic filtration